2022
DOI: 10.3390/jcm11133873
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of the Impact of Different Criteria for Sepsis Diagnosis on Outcome in Patients with Spontaneous Subarachnoid Hemorrhage

Abstract: Data on sepsis in patients with a subarachnoid hemorrhage (SAH) are scarce. We assessed the impact of different sepsis criteria on the outcome in an SAH cohort. Adult patients admitted to our ICU with a spontaneous SAH between 11/2014 and 11/2018 were retrospectively included. In patients developing an infection, different criteria for sepsis diagnosis (Sepsis-1, Sepsis-3_original, Sepsis-3_modified accounting for SAH-specific therapy, alternative sepsis criteria compiled of consensus conferences) were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In a relatively small cohort of 98 aSAH patients, Budohosky et al found a trend towards increased odds of DCI in patients with sepsis (OR=4.4, 95%CI: 0.08-25.2; p=0.095) 9 . Although the used sepsis operationalization was shown to be important in studies on sepsis-associated outcomes in critically ill patients in general 18,31 and in patients with aSAH specifically 2,32 , neither of the aforementioned studies included details about the utilized sepsis definition. Additionally, both studies were performed before 2016 9,14 and did not apply the updated sepsis-3 definition that focuses on septic organ dysfunction 15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a relatively small cohort of 98 aSAH patients, Budohosky et al found a trend towards increased odds of DCI in patients with sepsis (OR=4.4, 95%CI: 0.08-25.2; p=0.095) 9 . Although the used sepsis operationalization was shown to be important in studies on sepsis-associated outcomes in critically ill patients in general 18,31 and in patients with aSAH specifically 2,32 , neither of the aforementioned studies included details about the utilized sepsis definition. Additionally, both studies were performed before 2016 9,14 and did not apply the updated sepsis-3 definition that focuses on septic organ dysfunction 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Hypodensities on CT imaging resulting from ventricular catheter or intraparenchymal hematoma were not regarded as cerebral infarctions from DCI 6 . Clinical management was performed as described in detail previously and the procedures followed were in accordance with institutional guidelines 2,19 . Since January 2016, an updated protocol for standardized detection and management of DCI was implemented by the Department of Neurosurgery in line with our previous studies 1921 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon study inclusion, the dynamic of patients’ status was assessed every 8 h for a period of 5 days, resulting in up to 15 evaluation time points. The assessment followed sepsis-1/2 definition criteria (neither SIRS nor sepsis (0), SIRS (1), sepsis (2), severe sepsis (3), or septic shock (4); for a detailed list of diagnostic sepsis-1/2 definition criteria, see Supplementary Table S5 [ 39 , 40 , 41 ]). Due to the initiation time of the study, the original prospective recruitment strategy was based on the sepsis-1/2 definition.…”
Section: Methodsmentioning
confidence: 99%